RISK BASED CAPITAL (RBC) SEBAGAI INDIKATOR KESEHATAN KEUANGAN PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Ida Subaida; Rizka Gabriella Sandy; Nur Malika Putri (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to assess the financial health of insurance companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period using Risk-Based Capital (RBC) indicators. The assessment is conducted by calculating the solvency level, Minimum Solvency Limit (BTSM), and Risk Based Capital (RBC) based on the minimum RBC limit of 120%. The research method used is descriptive quantitative, utilizing secondary data in the form of annual financial reports of insurance companies listed on the IDX. The analysis results indicate that, in general, the majority of insurance companies are in a healthy financial condition, as their RBC values are above the minimum threshold. However, several companies, such as TUGU in 2022 and ASBI in 2023, fell below the RBC standard, reflecting pressure on their capital structure and high risk exposure during that period. Despite this, both companies demonstrated significant recovery in the following year. Meanwhile, other companies such as ABDA, LPGI, VINS, and ASRM maintained very high RBC values, demonstrating consistent capital strength and effective risk management. Overall, the RBC trend for the 2022–2024 period demonstrates that, despite fluctuations, the IDX-listed insurance industry maintains relatively stable financial resilience and is able to adapt to changing risks.